2005
DOI: 10.1073/pnas.0504412102
|View full text |Cite
|
Sign up to set email alerts
|

SyrB2 in syringomycin E biosynthesis is a nonheme Fe II α-ketoglutarate- and O 2 -dependent halogenase

Abstract: natural product biosynthesis ͉ enzymology ͉ organohalogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
354
0
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 319 publications
(376 citation statements)
references
References 33 publications
3
354
0
10
Order By: Relevance
“…Several other Fe II /αKG dioxygenases are purified as their apoprotein forms by inclusion of chelators (63,64). In contrast, some representatives of these enzymes have been purified anaerobically to assure that the metal remains in its reduced form (65,66).…”
Section: General Aspects Of Xana Activitymentioning
confidence: 99%
“…Several other Fe II /αKG dioxygenases are purified as their apoprotein forms by inclusion of chelators (63,64). In contrast, some representatives of these enzymes have been purified anaerobically to assure that the metal remains in its reduced form (65,66).…”
Section: General Aspects Of Xana Activitymentioning
confidence: 99%
“…[44][45][46][47] Aliphatic halogenases chlorinate the terminal methyl groups of amino acids tethered via thioester linkage to the phosphopantetheine cofactor of peptidyl-carrier proteins (PCPs). They require iron, αKG, oxygen, and chloride for their activity.…”
Section: αKg-dependent Halogenasesmentioning
confidence: 99%
“…Sequence analysis and the crystal structure of SyrB2 (14), the halogenase that supplies the 4-chloro-L-threonine fragment incorporated into syringomycin E (a phytotoxin produced by Pseudomonas syringae B301D) (12), revealed that it lacks the carboxylate ligand, having an Ala residue where the contributing Asp or Glu would normally be found (Scheme 1 A). The observation that a halide ion (X Ϫ ) coordinates to the Fe(II) cofactor at the vacated site suggested a related mechanism for the halogenase reaction involving abstraction of H • from the substrate by the oxo group of a haloferryl intermediate and rebound of the coordinated halogen radical from the resultant X-Fe(III)-OH complex to the substrate radical (green arrows).…”
mentioning
confidence: 99%
“…Before the recent discovery of the aliphatic halogenases (12), a group of ␣KG-dependent oxygenases that synthesize precursors for assembly of halogen-containing natural products by nonribosomal peptide synthetases (NRPSs), iron coordination by a conserved 2-histidine-1-carboxylate ''facial triad'' had been considered a defining feature of the family (13). Sequence analysis and the crystal structure of SyrB2 (14), the halogenase that supplies the 4-chloro-L-threonine fragment incorporated into syringomycin E (a phytotoxin produced by Pseudomonas syringae B301D) (12), revealed that it lacks the carboxylate ligand, having an Ala residue where the contributing Asp or Glu would normally be found (Scheme 1 A).…”
mentioning
confidence: 99%